The Impact of Company Size and Auditor Reputation on Auditor Switching (An Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange from 2018 to 2022) - saragih, Isabella acacia; Kurniawati, Elok (International Humanities and Applied Science Journal, 2025)
This research aims to analyze and obtain empirical evidence about the influence of firm size and auditor reputation on auditor switching. The independent variables used in this research are firm size and auditor reputation. The dependent variable used in this research is auditor switching. The data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange and the official websites of each company. The population used is all manufacturing companies registered on the IDX in 2018-2022. Using the Purposive Sampling sampling technique, a sample of 44 manufacturing companies listed on the Indonesia Stock Exchange was obtained. The data analysis method in this research uses Logistic Regression Analysis. The research results show that company size has a positive and significant effect on auditor switching and auditor reputation has a positive and significant effect on auditor switching in manufacturing companies listed on the IDX for the 2018 - 2022 per